2000
DOI: 10.1191/026921600701536192
|View full text |Cite
|
Sign up to set email alerts
|

Survival prediction in terminal cancer patients: a systematic review of the medical literature

Abstract: The clinical significance of studies on survival predictors in terminal cancer patients is hindered by both methodological limitations and the difficulty of finding common predictors for all final events in cancer related deaths. To evaluate the published medical literature concerned with the survival of patients with terminal cancer and identify potential prognostic factors, major electronic databases including MEDLINE (1966-), CANCERLIT (1983-) and EMBASE (1988-) were searched up to September 1999. Studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
177
1
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(193 citation statements)
references
References 49 publications
4
177
1
11
Order By: Relevance
“…22 Some authors have found that the presence or intensity of some physical symptoms (e.g., cognitive impairment, anorexia, xerostomia, dysphagia, and dyspnea) have independent prognostic importance in patients with a median survival of Ͻ 2 months. 23 Others have argued, however, that psychosocial measurements have dubious predictive value 24 -28 and that HRQoL measures (e.g., the Spitzer Quality of Life Index) cannot be used on their own to establish a prognosis in individual patients. 29 It is possible the validity and generalizability of these discrepant results may have been affected by methodological issues, such as a lack of precise criteria to define the onset of the terminal phase, difficulty in recruiting representative cohorts among patients with advanced or terminal cancer, and missing potential prognostic factors in the design of the study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Some authors have found that the presence or intensity of some physical symptoms (e.g., cognitive impairment, anorexia, xerostomia, dysphagia, and dyspnea) have independent prognostic importance in patients with a median survival of Ͻ 2 months. 23 Others have argued, however, that psychosocial measurements have dubious predictive value 24 -28 and that HRQoL measures (e.g., the Spitzer Quality of Life Index) cannot be used on their own to establish a prognosis in individual patients. 29 It is possible the validity and generalizability of these discrepant results may have been affected by methodological issues, such as a lack of precise criteria to define the onset of the terminal phase, difficulty in recruiting representative cohorts among patients with advanced or terminal cancer, and missing potential prognostic factors in the design of the study.…”
mentioning
confidence: 99%
“…26 -28,33,34 In addition, the prognostic factors considered often differ across studies, preventing possible evaluation of effects found by individual studies on these domains. 23 The current study was designed to overcome these limitations and to determine whether patient-rated and staff-rated QoL measurements in patients with cancer, who were seen at two different stages of their terminal phase, could be combined with medical data to predict survival.…”
mentioning
confidence: 99%
“…Grouping of the variables age, BMI, ECOG-ps, haemoglobin and white cell count was carried out using standard thresholds [22][23][24] . Survival analysis of the variables was performed using the Cox proportional hazard model.…”
Section: Discussionmentioning
confidence: 99%
“…The churches are opposed, although 78% of people of faith are in favour. 6 Those with disabilities are in favour (75%), while their representative organisations are against. 7 The medical bodies are mostly opposed, although more than two-thirds of GPs believe that the Royal College of General Practitioners should change its stance on the issue, subject to a number of safeguards.…”
Section: Assisted Death In the Ukmentioning
confidence: 99%
“…[6][7][8] Some patients even improve from a seemingly hopeless situation to resume an active and fulfilling existence. Oregon's own data since 1997 show a mean of 47 days from request to death by legalised PAS, with a range of 15 to 1,009 days, 9 despite the requirement of a prognosis of six months or less.…”
Section: Legalising Assisted Dying In the Ukmentioning
confidence: 99%